The Enzymatic and Non-Enzymatic Function of Myeloperoxidase (MPO) in Inflammatory Communication - Yulia Kargapolova; Simon Geißen; Ruiyuan Zheng; Stephan Baldus; Holger Winkels; Matti Adam (MDPI AG, 2021)
Myeloperoxidase is a signature enzyme of polymorphonuclear neutrophils in mice and humans. Being a component of circulating white blood cells, myeloperoxidase plays multiple roles in various organs and tissues and facilitates their crosstalk. Here, we describe the current knowledge on the tissue- and lineage-specific expression of myeloperoxidase, its well-studied enzymatic activity and incoherently understood non-enzymatic role in various cell types and tissues. Further, we elaborate on Myeloperoxidase (MPO) in the complex context of cardiovascular disease, innate and autoimmune response, development and progression of cancer and neurodegenerative diseases.